BALANCED SCORECARD IN MANUFACTURING COMPANY - Meutia Rahma; Sigit Handoyo (Universitas Ahmad Dahlan, 2017)
Due to the competitiveness in business world has been rising rapidly; the company must be able to enhance its performance in order to compete with other competitors. In measuring the performance, company should have a good performance measurement system that can assess the company’s performance comprehensively and appropriately. Balanced scorecard assessed to become a comprehensive and appropriate performance measurement systems that help the organization not only measure the performance but also manage the strategies. In this research, the researchers aim to analyze the current performance measurement systems applied in PT. Yokatta Indonesia as a sample. The type of research method is qualitative research and uses descriptive qualitative. Questionnaire has been tested for validity and reliability by using SPSS for Windows Release 19.0. Data analysis is used triangulation in combining several qualitative and quantitative data. From the results, performance measurement system balanced scorecard is being implemented in PT. Yokatta Indonesia not appropriately with considering some factors related with management style, additional costs, and also company infrastructures.